TACKLING THE NEGATIVE IMPACTS OF STUDENTS’ ADDICTION TO GOOGLE TRANSLATE - Fitria Hardini; Resti Citra Dewi (Institut Pendidikan Tapanuli Selatan, 2021)
Instant access and convenience provided by Google Translate have made it a very popular tool for students to learn especially for English language learners. Google Translate as one of the types of Mobile Assisted Language Learning can be accessed easily from a smartphone by students during the class. However, too much access to smartphone can also be counterproductive for students, especially during speaking practice. This study aims to describe the negative impacts of students' addiction due to Google Translate usage and how to tackle or minimize negative impacts during class. The study was conducted by using descriptive-qualitative method. The data was collected by distributing questionnaires and conducting class observation. The results show that there were negative impacts found due to students’ addiction to Google Translate usage during presentation class despite the benefits they gained. Anticipating or minimizing the overuse or misuse of Google Translate or any other type of translation application requires a commitment between the lecturer and students. The negative impacts can be tackled by setting class ground rules and state clear learning objectives before the class.